Answer

Verified

451.8k+ views

Hint- Here, we will proceed by simplifying the given function (which needs to be differentiated) with the help of a proper substitution.

Let the function be \[y = \left[ {{{\tan }^{ - 1}}\left( {\dfrac{x}{{\sqrt {{a^2} - {x^2}} }}} \right)} \right]\]

Put $x = a\sin \theta $ in the above function, we get

\[ \Rightarrow y = \left[ {{{\tan }^{ - 1}}\left( {\dfrac{{a\sin \theta }}{{\sqrt {{a^2} - {{\left( {a\sin \theta } \right)}^2}} }}} \right)} \right] = \left[ {{{\tan }^{ - 1}}\left( {\dfrac{{a\sin \theta }}{{\sqrt {{a^2}\left[ {1 - {{\left( {\sin \theta } \right)}^2}} \right]} }}} \right)} \right] = \left[ {{{\tan }^{ - 1}}\left( {\dfrac{{a\sin \theta }}{{a\sqrt {1 - {{\left( {\sin \theta } \right)}^2}} }}} \right)} \right]\]

As, we know that ${\left( {\sin \theta } \right)^2} + {\left( {\cos \theta } \right)^2} = 1 \Rightarrow 1 - {\left( {\sin \theta } \right)^2} = {\left( {\cos \theta } \right)^2}$

Using this above identity to simplify the function whose differentiation needs to be carried out

\[

\Rightarrow y = \left[ {{{\tan }^{ - 1}}\left( {\dfrac{{a\sin \theta }}{{a\sqrt {1 - {{\left( {\sin \theta } \right)}^2}} }}} \right)} \right] = \left[ {{{\tan }^{ - 1}}\left( {\dfrac{{\sin \theta }}{{\sqrt {{{\left( {\cos \theta } \right)}^2}} }}} \right)} \right] = \left[ {{{\tan }^{ - 1}}\left( {\dfrac{{\sin \theta }}{{\cos \theta }}} \right)} \right] = \left[ {{{\tan }^{ - 1}}\left( {\tan \theta } \right)} \right] = \theta \\

\Rightarrow y = \theta {\text{ }} \to {\text{(1)}} \\

\]

Also, we know that $x = a\sin \theta \Rightarrow \sin \theta = \dfrac{x}{a} \Rightarrow \theta = {\sin ^{ - 1}}\left( {\dfrac{x}{a}} \right){\text{ }} \to {\text{(2)}}$

Substituting the value obtained from equation (2) in equation (1), we get

\[ \Rightarrow y = {\sin ^{ - 1}}\left( {\dfrac{x}{a}} \right){\text{ }} \to {\text{(3)}}\]

Also we know that $\dfrac{{d\left[ {{{\sin }^{ - 1}}\left( {f\left( x \right)} \right)} \right]}}{{dx}} = \left[ {\dfrac{1}{{\sqrt {1 - {{\left( {f\left( x \right)} \right)}^2}} }}} \right] \times \left[ {\dfrac{{d\left( {f\left( x \right)} \right)}}{{dx}}} \right]$

Differentiating both sides of equation (3) with respect to $x$, we get

\[

\Rightarrow \dfrac{{dy}}{{dx}} = \dfrac{{d\left[ {{{\sin }^{ - 1}}\left( {\dfrac{x}{a}} \right)} \right]}}{{dx}}{\text{ = }}\left[ {\dfrac{1}{{\sqrt {1 - {{\left( {\dfrac{x}{a}} \right)}^2}} }}} \right] \times \left[ {\dfrac{{d\left( {\dfrac{x}{a}} \right)}}{{dx}}} \right] = \left[ {\dfrac{1}{{\sqrt {\left( {\dfrac{{{a^2} - {x^2}}}{{{a^2}}}} \right)} }}} \right] \times \left[ {\dfrac{1}{a}} \right] = \left[ {\dfrac{a}{{\sqrt {{a^2} - {x^2}} }}} \right] \times \left[ {\dfrac{1}{a}} \right] \\

\Rightarrow \dfrac{{dy}}{{dx}} = \dfrac{1}{{\sqrt {{a^2} - {x^2}} }} \\

\]

Therefore, the differentiation of the given function \[\left[ {{{\tan }^{ - 1}}\left( {\dfrac{x}{{\sqrt {{a^2} - {x^2}} }}} \right)} \right]\], with respect to $x$ is \[\dfrac{1}{{\sqrt {{a^2} - {x^2}} }}\].

Note- In this problem we have especially substituted $x = a\sin \theta $ because due to this substitution, the function inside the tangent inverse will be converted into tangent so that these two will cancel out with each other and we will be left with the angle which is in a much simplified form.

Let the function be \[y = \left[ {{{\tan }^{ - 1}}\left( {\dfrac{x}{{\sqrt {{a^2} - {x^2}} }}} \right)} \right]\]

Put $x = a\sin \theta $ in the above function, we get

\[ \Rightarrow y = \left[ {{{\tan }^{ - 1}}\left( {\dfrac{{a\sin \theta }}{{\sqrt {{a^2} - {{\left( {a\sin \theta } \right)}^2}} }}} \right)} \right] = \left[ {{{\tan }^{ - 1}}\left( {\dfrac{{a\sin \theta }}{{\sqrt {{a^2}\left[ {1 - {{\left( {\sin \theta } \right)}^2}} \right]} }}} \right)} \right] = \left[ {{{\tan }^{ - 1}}\left( {\dfrac{{a\sin \theta }}{{a\sqrt {1 - {{\left( {\sin \theta } \right)}^2}} }}} \right)} \right]\]

As, we know that ${\left( {\sin \theta } \right)^2} + {\left( {\cos \theta } \right)^2} = 1 \Rightarrow 1 - {\left( {\sin \theta } \right)^2} = {\left( {\cos \theta } \right)^2}$

Using this above identity to simplify the function whose differentiation needs to be carried out

\[

\Rightarrow y = \left[ {{{\tan }^{ - 1}}\left( {\dfrac{{a\sin \theta }}{{a\sqrt {1 - {{\left( {\sin \theta } \right)}^2}} }}} \right)} \right] = \left[ {{{\tan }^{ - 1}}\left( {\dfrac{{\sin \theta }}{{\sqrt {{{\left( {\cos \theta } \right)}^2}} }}} \right)} \right] = \left[ {{{\tan }^{ - 1}}\left( {\dfrac{{\sin \theta }}{{\cos \theta }}} \right)} \right] = \left[ {{{\tan }^{ - 1}}\left( {\tan \theta } \right)} \right] = \theta \\

\Rightarrow y = \theta {\text{ }} \to {\text{(1)}} \\

\]

Also, we know that $x = a\sin \theta \Rightarrow \sin \theta = \dfrac{x}{a} \Rightarrow \theta = {\sin ^{ - 1}}\left( {\dfrac{x}{a}} \right){\text{ }} \to {\text{(2)}}$

Substituting the value obtained from equation (2) in equation (1), we get

\[ \Rightarrow y = {\sin ^{ - 1}}\left( {\dfrac{x}{a}} \right){\text{ }} \to {\text{(3)}}\]

Also we know that $\dfrac{{d\left[ {{{\sin }^{ - 1}}\left( {f\left( x \right)} \right)} \right]}}{{dx}} = \left[ {\dfrac{1}{{\sqrt {1 - {{\left( {f\left( x \right)} \right)}^2}} }}} \right] \times \left[ {\dfrac{{d\left( {f\left( x \right)} \right)}}{{dx}}} \right]$

Differentiating both sides of equation (3) with respect to $x$, we get

\[

\Rightarrow \dfrac{{dy}}{{dx}} = \dfrac{{d\left[ {{{\sin }^{ - 1}}\left( {\dfrac{x}{a}} \right)} \right]}}{{dx}}{\text{ = }}\left[ {\dfrac{1}{{\sqrt {1 - {{\left( {\dfrac{x}{a}} \right)}^2}} }}} \right] \times \left[ {\dfrac{{d\left( {\dfrac{x}{a}} \right)}}{{dx}}} \right] = \left[ {\dfrac{1}{{\sqrt {\left( {\dfrac{{{a^2} - {x^2}}}{{{a^2}}}} \right)} }}} \right] \times \left[ {\dfrac{1}{a}} \right] = \left[ {\dfrac{a}{{\sqrt {{a^2} - {x^2}} }}} \right] \times \left[ {\dfrac{1}{a}} \right] \\

\Rightarrow \dfrac{{dy}}{{dx}} = \dfrac{1}{{\sqrt {{a^2} - {x^2}} }} \\

\]

Therefore, the differentiation of the given function \[\left[ {{{\tan }^{ - 1}}\left( {\dfrac{x}{{\sqrt {{a^2} - {x^2}} }}} \right)} \right]\], with respect to $x$ is \[\dfrac{1}{{\sqrt {{a^2} - {x^2}} }}\].

Note- In this problem we have especially substituted $x = a\sin \theta $ because due to this substitution, the function inside the tangent inverse will be converted into tangent so that these two will cancel out with each other and we will be left with the angle which is in a much simplified form.

Recently Updated Pages

How many sigma and pi bonds are present in HCequiv class 11 chemistry CBSE

Why Are Noble Gases NonReactive class 11 chemistry CBSE

Let X and Y be the sets of all positive divisors of class 11 maths CBSE

Let x and y be 2 real numbers which satisfy the equations class 11 maths CBSE

Let x 4log 2sqrt 9k 1 + 7 and y dfrac132log 2sqrt5 class 11 maths CBSE

Let x22ax+b20 and x22bx+a20 be two equations Then the class 11 maths CBSE

Trending doubts

Which are the Top 10 Largest Countries of the World?

Fill the blanks with the suitable prepositions 1 The class 9 english CBSE

How many crores make 10 million class 7 maths CBSE

The 3 + 3 times 3 3 + 3 What is the right answer and class 8 maths CBSE

Difference between Prokaryotic cell and Eukaryotic class 11 biology CBSE

Difference Between Plant Cell and Animal Cell

Give 10 examples for herbs , shrubs , climbers , creepers

Change the following sentences into negative and interrogative class 10 english CBSE

Write a letter to the principal requesting him to grant class 10 english CBSE